Rhodol Derivatives as Selective Fluorescent Probes for the Detection of HgII Ions and the Bioimaging of Hypochlorous Acid. Issue 2 (6th December 2017) - Li, Ling; Wang, Shu; Lan, Hongxia; Gong, Guiyi; Zhu, Yifan; Tse, Yu Chung; Wong, Keith Man‐Chung
Abstract: Two sensors, 1 with a spirolactone group and2 with a spirolactam group containing a phenyl isothiocyanate moiety, based on rhodol, were designed and synthesized in order to obtain materials with excellent optical properties for the detection of environmentally and biologically important Hg 2+ and hypochlorous acid (HClO) ions. The crystal structure of1 revealed two moieties, a rhodamine‐like portion with a spirolactone and a fluorescein‐like portion without a spirolactone. In the absence of analyte, 1 produced an optical output with a maximum absorption and emission at 475 and 570 nm, respectively, which was attributed to the fluorescein‐like moiety without a spirolactone. In contrast, the rhodamine‐like moiety containing a spirolactone was activated by the addition of H + or Hg 2+ ions, and1 yielded new absorption and emission peaks at 530 and 612 nm, respectively. Further functionalization with a phenyl isothiocyanate group afforded2, a fluorescent probe for HClO. High selectivity and sensitivity towards the hypochlorite ion were anticipated, owing to the stoichiometric and irreversible formation of a thiosemicarbazide group, which led to dramatic fluorescence responses. With good functionality at physiological pH, probe2 was successfully used to image HClO in HeLa cells. Abstract : Get the picture : A series of rhodol derivatives with extended π conjugation are reported to give selective sensing properties. Those functionalized with a phenyl isothiocyanate group can serve as a fluorescent probe for bioimaging of endogenous HClO within HeLa cells.